One new genus of cockroach in the Neotropical subfamily Nyctiborinae (Dictyoptera: Blattodea: Ectobiidae) - Vélez-Bravo, Andrés (Zootaxa, 2013)
The genus Nyctantonina gen. nov. and its two species Nyctantonina breviclasma sp. nov. and Nyctantonina pteromacro-tata sp. nov. are described and illustrated. Dichotomous key to identify the species of genus is given.